THE EFFECTIVENESS OF THE RING DEBATE STRATEGY IN LEARNING THE TECHNICAL PERFORMANCE OF THE SKILL OF NETTER LIFTING IN WEIGHTLIFTING - Qusay Rashid Sabti; Thabit Bdaiwi Oudah (Proximus Journal Publishing, 2025)
The teaching methods are one of the principles and rules that guide the procedures followed by the teacher for the purpose of organizing what students have from previous experiences, the education process is an essential pillar to achieve learning in line with the different positions to form the strategy and achieve the goals through what it does, and the research aimed to prepare an educational curriculum using the strategy of the ring debate for students of the first stage of the Faculty of Physical Education and Sports Sciences and to identify the impact of the effectiveness of the strategy in learning the technical performance of the elevation of the netter, The research was applied to a sample of 30 students of the first stage, they were divided into two equal and equivalent groups of control and experimental by 15 students per group, the researcher took into account the homogeneity procedure in the factors affecting such as height, weight and age, and the ring strategy took a period of time of (6) weeks and according to the college curriculum, and the researcher reached conclusions, the most important of which is the superiority of the ring debate strategy on the approach used in learning the technical performance of the elevation of the netter for students.
Keywords: ring debate; learning; nettress